KEEFEKTIFAN PEMBELAJARAN KONSEP KIMIA LARUTAN DENGAN MENERAPKAN MODEL PENGGAMBARAN MIKROSKOPIS DI MAN KABUPATEN PIDIE - Azhar Azhar (Lantanida Journal, 2017)
The microscopic concept in chemistry learning can not be obtained directly from the experience or sensory observations. To understand this microscopic concept requires complex intellectual engagement. One way to facilitate learners in understanding the concept of microscopic is by using the appropriate modeling or learning media. In the study of chemical solution, so that learners easy to understand the concept of the microscopic can use a model picture called the microscopic model of depiction. This study aims to examine the effectiveness of learning chemical concept of solution by applying the model of microscopic depiction as well as to know the student's response to microscopic modeling in MAN Kabupaten Pidie Aceh Province. The research design used in this research is quasi experimental design. The results showed that by applying microscopic modeling model can streamline the learning process of chemical solution in MAN Kabupaten Pidie. Furthermore, MAN students in Kabupaten Pidie have a positive response to the application of microscopic modeling of learning chemistry of solution because students feel easier in understanding the chemical concept of solution